Concurrent changes in Dunaliella salina ultrastructure and membrane phospholipid metabolism after hyperosmotic shock (The Rockefeller University Press, 1988)
Hyperosmotic shock, induced by raising the NaCl concentration of Dunaliella salina medium from 1.71 to 3.42 M, elicited a rapid decrease of nearly one-third in whole cell volume and in the volume of intracellular organelles. The decrease in cell volume was accompanied by plasmalemma infolding without overall loss of surface area. This contrasts with the dramatic increase in plasmalemma surface area after hypoosmotic shock (Maeda, M., and G. A. Thompson. 1986. J. Cell Biol. 102:289-297). Although plasmalemma surface area remained constant after hyperosmotic shock, the nucleus, chloroplast, and mitochondria lost membrane surface area, apparently through membrane fusion with the endoplasmic reticulum. Thus the endoplasmic reticulum serves as a reservoir for excess membrane during hyperosmotic stress, reversing its role as membrane donor to the same organelles during hypoosmotically induced cell expansion. Hyperosmotic shock also induced rapid changes in phospholipid metabolism. The mass of phosphatidic acid dropped to 56% of control and that of phosphatidylinositol 4,5-bisphosphate rose to 130% of control within 4 min. Further analysis demonstrated that within 10 min after hyperosmotic shock, there was 2.5-fold increase in phosphatidylcholine turnover, a twofold increase in lysophosphatidylcholine mass, a four-fold increase in lysophosphatidate mass, and an elevation in free fatty acids to 124% of control, all observations suggesting activation of phospholipase A. The observed biophysical and biochemical phenomena are likely to be causally interrelated in providing mechanisms for successful accommodation to such severe osmotic extremes.